Medidas socioeducativas en adolescentes infractores: la psicoeducación como estrategia de cambio - Acencio-Malpartida, Larry Franklin (2024)
Objective. Was to understand the experiences of adolescent offenders while participating in a psychoeducational intervention as part of fulfilling a socio-educational measure imposed at the penal level. Methods. This qualitative study adheres to coherence within the sociocritical paradigm, leading to the development of a participatory research-action design. Such actions focus on a process of methodological rigor; thus, it has been necessary to observe information saturation through triangulation of information sources. Participants included 10 adolescents in conflict with the penal law (ACLP, by its Spanish acronym), along with 10 parents and/or guardians, as well as professionals involved in psychoeducational intervention. Data were collected through interviews, discussion groups, and team meetings, conducted virtually using a semi-structured interview guide, recorded in audio format. Subsequently, data underwent open, axial, and selective categorization and coding. Results. A detailed understanding of the change experience through psychoeducation, as narrated in the adolescent interviews, was obtained. Conclusions. It has been evidenced that the psychoeducational experience in adolescents generates changes in their development and their environment; furthermore, the analysis of the evolution and change of an adolescent offender has been conducted.